A 3D Organically Synthesized Porous Carbon Material for Lithium‐Ion Batteries. (4th July 2018) - Zhao, Ziqiang; Das, Saikat; Xing, Guolong; Fayon, Pierre; Heasman, Patrick; Jay, Michael; Bailey, Steven; Lambert, Colin; Yamada, Hiroki; Wakihara, Toru; Trewin, Abbie; Ben, Teng; et al.
Abstract: We report the first organically synthesized sp–sp 3 hybridized porous carbon, OSPC‐1. This new carbon shows electron conductivity, high porosity, the highest uptake of lithium ions of any carbon material to‐date, and the ability to inhibit dangerous lithium dendrite formation. The new carbon exhibits exceptional potential as anode material for lithium‐ion batteries (LIBs) with high capacity, excellent rate capability, long cycle life, and potential for improved safety performance.